Análise das relações entre propriedades físicas e mecânicas em diferentes regiões de extração da madeira de Cambará (Erisma Uncinatum Warm) - Aquino, Vinicius Borges de Moura (2019)
This research had the purpose of evaluating the relationship between the physical and mechanical properties of Cambará wood extracted from three distinct sites: Vera, Mucajaí and south of Rondônia. The possibility of estimating (linear regression, exponential, geometric and logarithmic models) the physical and mechanical properties as a function of apparent density will also be evaluated. This research was motivated by the fact that there is no consideration in the normative code the influence of the extraction regions on the physical and mechanical properties of timber, since different climatic conditions, vegetation and soil in which the tree can influence their growth and, consequently, the values of its physical and mechanical properties. The ABNT NBR 7190, the Kruskal-Wallis variance analysis and the resampling technique were considered in the accomplishment of the procedures. The results of ANOVA indicated an equivalence index equal to 100% for the properties of the Vera region, 94% for the regions of Mucajaí and South of Rondônia. The resampling technique led to similar results for the Vera and Mucajaí regions and for the southern region of Rondônia, the equivalence index was equal to 89%. The results of the ANOVA to estimate the physical and mechanical properties in function of the apparent density indicated that it was not possible to make such estimates for Cambará wood.